1999
DOI: 10.1021/ma9910585
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Using Small-Angle X-ray Scattering and Solid-State NMR of Microdomain Structures in Poly(styrene−butadiene−styrene) Triblock Copolymers

Abstract: The complementary techniques of solid-state NMR and small-angle X-ray scattering (SAXS) have been used to determine the microdomain structures of a series of commercial poly(styrene-b-butadiene-b-styrene) triblock copolymers with different molecular weights. The relative locations of multiple scattering peaks, indirect transform, and Porod analysis have been used to determine the morphology and the sizes of various domains as well as the interfacial thickness between them. Solid-state NMR of 1H spin diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…8 Our results concerning the relaxation behavior of the soft segment for the block copolymers were in good agreement with their results. Similar observations have been also reported in a number of systems, such as poly(styrene-b-butadiene-b-styrene), 9 segmented polyesters 15,16 and polymethacrylate tethered on silica particles. 17,18 Figure 2(a) shows the temperature dependence of the relaxation time for component A.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…8 Our results concerning the relaxation behavior of the soft segment for the block copolymers were in good agreement with their results. Similar observations have been also reported in a number of systems, such as poly(styrene-b-butadiene-b-styrene), 9 segmented polyesters 15,16 and polymethacrylate tethered on silica particles. 17,18 Figure 2(a) shows the temperature dependence of the relaxation time for component A.…”
Section: Resultssupporting
confidence: 87%
“…They also measured the thickness of poly(styrene-b-butadieneb-styrene) triblock copolymers under the same assumption using the same technique. 9 The interfacial thickness obtained in these investigations was in good agreement with those obtained by SAXS. Furthermore, Lin and Blum reported that the relaxation time of polymethacrylate tethered on silica particles was the same as that of bulk polymethacrylate.…”
Section: Resultssupporting
confidence: 84%
“…For the system under study, the spin diffusion coefficients were reported as 0.05 nm 2 · ms −1 and 0.80 nm 2 · ms −1 for PB and PS components, respectively 39. An estimate of the rms displacement of magnetization,〈 x 2 〉 1/2 , following Einstein's relation 〈 x 2 〉 = 2 Dt in one dimension (taking account of the lamellar structure of the system), leads to rms values of 2 nm and 9 nm for PB and PS, respectively, for an exemplary time scale of 50 ms which represents a T 1 value at intermediate frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…When the constant background term C 0 is removed [40], the slope obtained at high q can be used to obtain a measure of the specific surface area (S/V), assuming an ideal, sharp interface between the void and the metal matrix. However, when a diffuse interface is encountered, the meaning of S/V is not well defined and obtaining an estimate of interfacial thickness is then more meaningful.…”
Section: Void-metal Matrix Interface Structurementioning
confidence: 99%